Functional polymorphisms in transforming growth factor-beta-1 (TGFβ-1) and vascular endothelial growth factor (VEGF) genes modify risk of renal parenchymal scarring following childhood urinary tract infection - Hussein, Almontaser; Askar, Eman; Elsaeid, Moustafa; Schaefer, Franz (Nephrology, dialysis, transplantation, 2010)
Background. The risk of renal scar formation following urinary tract infection (UTI) varies markedly between individuals. We sought to investigate a possible role of the common polymorphisms in the gene encoding for VEGF and TGFβ-1, key regulators of tissue repair, in renal scarring.Methods. Acute pyelonephritis was diagnosed in 104 children (63 males) aged 2 months to 12 years by urine culture and 99Tc-DMSA renal scan. A follow-up isotope scan was performed 4-6 months later to identify new renal scar formation. Vesicoureteral reflux (VUR) was examined by micturating cystourethrogram. Controls comprised 300 healthy children with no evidence of renal disease. Three single-nucleotide polymorphisms (SNPs) in the TGFβ-1 (−800 A/G, −509 C/T and 869 C/T) and four SNPs in the VEGF gene (−2578 C/A, −1154 G/A, −460 T/C and +405 G/C) were genotyped in all subjects.Results. Forty-six of the 104 patients developed renal parenchymal scarring (44.2%). VUR was found in 35.6%. The −509 T allele in the TGFβ-1 promoter was significantly more common in cases with renal scarring (51%) than in non-scarring patients (22.4%) and controls (23.6%) (both P < 0.0001). At the haplotype level, the GTC combination at −800/−509/+869 was strongly associated with renal scarring (P = 0.0002). VEGF−460 CC was more common in UTI cases with renal scarring than in non-scarring patients and controls (P = 0.03 and 0.001, respectively). Multiple logistic regression testing identified the presence of VUR (odds ratio 12.4, CI 3.8-40; P < 0.001) and the TGFβ-1 −509 T allele (OR 6.1, CI 2.4-15.5; P < 0.001) as independent risk factors for renal scarring after UTI. In contrast, age, gender and the type of underlying organism were not predictive of renal scarring.Conclusions. Activating variants in the TGFβ-1 and VEGF gene promoters are associated with post-UTI renal scar formation in children. The TGFβ-1 509T allele predicts renal scarring independent of VUR.